PAST: accurate instrumentation on fully optimized program. (16th January 2015) - Yin, Jie; Ma, Chao; Hu, Shi‐Min
Summary: Instrumentation is a powerful technique for monitoring, profiling, debugging, logging and tracing the software. In order to determine the instrumentation location, the user needs to know where the current executed location is in the source code. Previous instrumentation approaches rely on debugging information to find the location in the source code. For fully optimized programs, debugging information is not complete, which limits the application of those approaches. In this paper, we present pattern‐based abstract syntax tree (PAST) instrumentation, an ideal instrumentation methodology that accurately instruments the fully optimized program. The instrumentation location is specified in an intuitive way that matches the source code at the abstract syntax tree level. The program can be instrumented either at the compile time using the ordinary compiling or when it is running using the just‐in‐time compiling. Experimental results show that PAST can accurately instrument the target program. There is negligible run time overhead when the running program is instrumented without any operation. We have implemented PAST on both x86‐32 and x86‐64 to show that PAST is easily portable across different architecture. Copyright © 2015 John Wiley & Sons, Ltd.